AKTIVITAS AKTIF SISWA DALAM PEMBELAJARAN MATEMATIKA REALISTIK - Ahmad, Marzuki (Institut Pendidikan Tapanuli Selatan, 2016)
This research aimed to describe the activity of students active learning approach for the implementation of Realistic Mathematics Education (RME). This type of research is descriptive research with quantitative, The subjects are students of SMP Negeri 15 Medan, class VII (6) with total of 40 people, The instruments used are the Observation Sheet Activities Active Students who applied in four (4) times the implementation learning with approach of PMR. This data in the research were analyzed use descriptive statistics. The results showed that the activity of students with Realistic Mathematics Education (RME) meets the criteria of effective. Where from the tenth aspect of students activity observed include read/ understand (book/ LAS), attention to the explanation of the teacher, to solve the problems, asking questions, discussions among students, discussion between students and teachers, explain a results/ an expression/ an idea, write things that are relevant or importan to the learning activities, making conclusion, fortofolio (do the work a task themeselves ) within the tolerance limits ideal. This learning make students more enthusiastic in learning, growing cooperation in learning and attitude respect each other opinions or ideas. There are also students who are more willing to submit respons , opinions and give questions to the friends or the teacher. Based on research of this results, the researchers suggested that the Realistic Mathematics Education (RME) is used in learning because of RME is an alternative to increasing the activity of studentsâ activity in learning